Os sistemas de parentesco e suas recomposições - Virginia Lúcia Souto Maior Sanábio (2019)
Contemporary family recompositions are not constituted by the traditional matrimonial system. Configure a broad, controversial, and intensely debated theme in several knowledge areas. Because of its breadth, this theme was circumscribed to the notion of socio-affective parenting, which in general refers to substitute families. This work is based on the hypothesis in which the French psychoanalyst Jacques Lacan (1901-1981) predicts the recompositions and mutations of contemporary family members. With this, an epistemological cut is made to ask if the psychoanalysis of Lacanian orientation would have theoretical and clinical instruments to operate on the contemporary families. In order to delimit this work’s methodological field, it is discussed: Is the family necessarily Oedipal? Are the contemporary families sustained by the love to the father? What are the elements that remain invariant in family formation? After pointing out the path of this research, the work continues from a review of traditional systems of family formation, in order to situate their mode of organization and customs. The universality of the rule of exogamy in societies is investigated by a detailed study of Claude Lévi-Strauss's thesis on the elemental structures of kinship. The choice of this theorist is due to the importance and influence of the structural method in the early Lacan’s works. After revisiting some classical authors, it becomes apparent that the formulations used for the study of traditional kinship organizations are not enough for the study of present-day family recompositions. The new arrangements, present in contemporary families, have their roots in the decline of patriarchalism, changes in social customs and sexual liberalization. From this, we investigate how the family theme was treated in Lacanian teaching, from the influence of Durkheim's sociology to the influence of Lévi-Strauss's structuralism. The goal of taking this way in Lacanian theory was to go beyond Oedipus, towards a logicization. Finally, the subject of this research is submitted to the juridical field, in particular to Brazilian jurisprudence. The parenting inscribes the passage from the universal to the particular, exemplified in the legal context, where the actions are related to socio-affective parenting. Lacan, for his part, demonstrates that the object a resists the universalizing operation of the Name-of-Father. He shows the relativity character of the paternal function and pluralizes the Name-of-the-Father.